2021
DOI: 10.21203/rs.3.rs-1083803/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Challenges in Providing Health Care Services During COVID-19 Pandemic: Exploration of Providers’ Perspectives in Nepal.

Abstract: IntroductionThe rapid increase of COVID-19 cases since the beginning of May 2020, imposition of lockdown, and preparation activities to detect, manage and treat COVID-19 in public hospitals have impacted on the provision of non-COVID health care services resulting in increased morbidity and mortality in Nepal. This study aims to explore challenges in providing non-COVID as well as COVID-19 health care services through public hospitals in Eastern Nepal.MethodsA qualitative study with 25 key informants from thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…In our study, the participants reported that the existing human resources were inadequate which appeared as a major challenge in providing COVID-19 services. These findings have been supported by the previous studies [ 34 , 39 , 40 ] where the existing health workers were divided to provide both COVID-19 and non-COVID health care services. The doctors were insufficient in number and there was no additional health workers for substitution.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our study, the participants reported that the existing human resources were inadequate which appeared as a major challenge in providing COVID-19 services. These findings have been supported by the previous studies [ 34 , 39 , 40 ] where the existing health workers were divided to provide both COVID-19 and non-COVID health care services. The doctors were insufficient in number and there was no additional health workers for substitution.…”
Section: Discussionsupporting
confidence: 84%
“…Due to the lack of ventilators, ICU and X-ray services, health facilities were unable to manage the critical cases in an effective manner. These findings are supported by the studies [ 34 , 40 ] where hospitals had to run the services in the limited resources such as isolation beds, ICUs and ventilators, oxygen plant, PPEs etc. The existing buildings, other infrastructure and equipment were reportedly made worse by the COVID-19.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation